PERSEPSI MASYARAKAT TERHADAP DIKEMBANGKANNYA DESA BONGAN SEBAGAI DESA WISATA DI KABUPATEN TABANAN - Putra, Agus Muriawan; Sutaguna, I Nyoman Tri (Jurnal Analisis Pariwisata, 2021)
Bongan village has a variety of uniqueness that can be used as a tourist attraction, both natural, cultural, culinary and spiritual attractions. Some of the uniqueness or attractiveness of Bongan Village are: 1) Ngaben Tikus Ceremony, where this ceremony has been carried out for generations since the days of the Tabanan Kingdom. This special ceremony starts from the Puseh Temple area of Adat Bedha Village; 2) Bongan Village also has the potential to be a tourist attraction for Bali Starling. This was supported by the breeding of the Bali Starling Bird; 3) Balang Tamak Temple, related to the character of Pan Balang Tamak; and 4) Mesuryak tradition is a unique tradition that is still carried out from generation to generation in Bongan Village. A qualitative approach with a combination of Focus Group Discussion (FGD), SWOT Matrix, and Likert Scale Analysis will find various opinions or perceptions of the Bongan community related to the development of Bongan Village as a rural tourist in Tabanan Regency. The results of the data analysis will be presented in a descriptive qualitative manner that presents the opinions / perceptions of the community, the results of observations, theories, and concepts found in the field based on the informants' point of view which are then interpreted by the Research Team. Keywords: Community Perception, Rural Tourism Development, Community Tourism